KEBEBASAN BERAGAMA DALAM PASAL 28E UUD 1945 DAN TOLERANSI BERDASARKAN HR. BUKHORI NO. 39: FREEDOM OF RELIGION IN ARTICLE 28E OF THE 1945 CONSTITUTION AND TOLERANCE BASED ON HR. BUKHORI NO. 39 - Al Khansa, Amelia Cendikia; Arifin, Tajul (Fakultas Hukum Universitas Trisakti, 2025)
Abstract This study aims to discuss the spread of the issue of religious freedom in the context of Indonesian national law, especially through Article 28E of the 1945 Constitution, as well as the values of tolerance in Islam as reflected in the Hadith Narrated by Bukhori No. 39. The main purpose of this discussion is to evaluate the extent to which the state constitution and Islamic teachings provide support for the principles of freedom and tolerance between religions in a diverse society. Through normative juridical approaches and literature study methods, the results of the study show that religious freedom is part of human rights that are not only guaranteed by the constitution, but also supported by Islamic teachings that emphasize the importance of tolerance. Despite this, in practice, there are still several challenges, such as discriminatory treatment of minority groups and restrictions on the exercise of religious rights. Therefore, synergy is needed between the state's role and public awareness in creating a harmonious religious life, mutual respect, and respect for differences.